The use of unmanned aerial vehicles in the second world war: military-historical aspect and international legal regulation - Похиленко, Ірина; Акімов, Михайло (My University, 2025)
This article is concerning on comprehensive analysis of the use of unmanned aerial vehicles during the Second World War with regard to militaryhistorical aspects, provisions of international humanitarian law at that time, the technical capabilities of the belligerent states and the prerequisites for further development of the regulatory framework for the use of these latest means of warfare. The peculiarities of the legal status of unmanned aerial vehicles in the period from 1939 to 1945 have been studied; the relationship between technological progress and the provisions of international law has been established; the practice of using unmanned aerial vehicles by different states in terms of international law in force at that time has been examined. The scientific novelty consists in the attempt to combine historical and legal analysis with the study of the development of military technologies in the Second World War for the first time on an interdisciplinary level and to define whether the use of unmanned aerial vehicles (e.g., pilotless guided bombs, target drones, etc.) complied with the principles and norms of international humanitarian law of that time. The article also examines how the events of 1939-1945 influenced the formation of current international legal regime on autonomous and remotely controlled weapons. It has been found that at the time of the Second World War, international law did not contain separate rules on the use of unmanned aerial vehicles. However, even then, some principles of this field of law – in particular, the principles of proportionality, necessity and protection of civilians – had to be applied to new means of warfare. The absence of proper legal regulation created gaps that remain in part to this day in the context of autonomous weapons systems. The experience of the Second World War proves the need to constantly update international law in line with technological progress. Particular attention should be paid to the ethical aspects of unmanned aerial vehicles, which, although not subject to international regulation in 1939-1945, are now becoming particularly relevant Ця стаття присвячена комплексному аналізу використання безпілотних літальних апаратів під час Другої світової війни з урахуванням військово-історичних аспектів, положень міжнародного гуманітарного права того часу, технічних можливостей воюючих держав та передумов для подальшого розвитку нормативно-правової бази використання цих новітніх засобів ведення війни. Розглянуто особливості правового статусу безпілотних літальних апаратів у період з 1939 по 1945 роки, встановлено взаємозв’язок між технічним прогресом та положеннями міжнародного права, проаналізовано практику використання безпілотних літальних апаратів різними державами з точки зору міжнародного права, що діяло на той час. Уперше на міждисциплінарному рівні зроблено спробу поєднати історико-правовий аналіз з дослідженням розвитку військових технологій у Другій світовій війні та встановити, чи відповідало застосування безпілотних літальних апаратів (зокрема, безпілотних керованих бомб, дронів-мішеней тощо) принципам і нормам тогочасного міжнародного гуманітарного права. Також розглянуто вплив подій 1939-1945 років на формування сучасного міжнародно-правового режиму автономної та дистанційно керованої зброї. Встановлено, що на час Другої світової війни міжнародне право не містило окремих норм щодо застосування безпілотних літальних апаратів. Проте вже тоді деякі принципи цієї галузі права – зокрема, принципи пропорційності, необхідності та захисту цивільного населення – доводилося застосовувати до нових засобів ведення війни. Відсутність належного правового регулювання в контексті автономних систем озброєнь створила прогалини, що частково залишаються і донині. Досвід Другої світової війни доводить необхідність постійного оновлення міжнародного права відповідно до технічного прогресу. Особливу увагу слід приділити етичним аспектам використання безпілотних літальних апаратів, що, хоч і не були предметом міжнародного регулювання в 1939-1945 роках, зараз набувають особливої актуальності.
Застосування безпілотних літальних апаратів у другій світовій війні: військово-історичний аспект та міжнародно-правове регулювання
Keywords: unmanned aerial vehicles; Second World War; international humanitarian law; international legal regulation; military technologies; autonomous systems; aviation activity; безпілотні літальні апарати; Друга світова війна; міжнародне гуманітарне право; міжнародно-правове регулювання; військові технології; автономні системи; авіаційна діяльність; 623.746“1939/1945”(100):341.3